Incidental Detection of Sacral Insufficiency Fracture on 68Ga-FAPI PET/MR. (December 2021) - Lv, Yuhu; Lan, Xiaoli; Qin, Chunxia
Abstract : Abstract: A 61-year-old woman with low-set rectal adenocarcinoma (cT4bN1Mx) received radiotherapy and chemotherapy for 4 months, and then she underwent 18 F-FDG PET/CT and 68 Ga-FAPI PET/MR. Obviously increased 68 Ga-FAPI uptake was unexpectedly revealed on both sides of the sacrum with low 18 F-FDG uptake, which was diagnosed as insufficiency fracture based on the imaging features, advanced patient age, and radiotherapy history. The possibility of insufficiency fracture should be considered when accidental, symmetrically increased sacral 68 Ga-FAPI uptake appears in cancer patients, and differential diagnosis should be carefully made.